Analisis Kegiatan Paket Wisata Sekolah Dengan Metode Line Of Balance Pada Industri Pariwisata - Haryadi Sarjono; Indra Patria; Agung Sudjatmoko; Delvia Safitri (Universitas Negeri Padang, 2023)
Dkandang Amazing Farm is a brand that represents the products of CV Sawangan Dairy Farm. The products sold are goods and services. The service product offered by Dkandang is educational tourism. The existence of educational tours creates new value in offering products that are at CV Sawangan Dairy Farm. However, in implementing tour package activities, there are several obstacles, such as congestion in some activities so that the tour packages become hampered and the activities are not on time from the specified time. This study aims to analyze the activities of tour packages with the Line of Balance method. Researchers took samples by asking directly for data owned by the Tourism team for further analysis. For the first step, the data is processed in a planning S Curve to be re-analyzed to find activities that experience delays in tour package activities. Next, a Logic Diagram explains the sequence of activities from start to finish. The last step is to make a Line of Balance Diagram. The results show that the S curve can analyze the problems in tour package activities. In addition, a Line of Balance can be used to evaluate schedules or make plans for tour package activities.